2008
DOI: 10.1590/s1413-73722008000200006
|View full text |Cite
|
Sign up to set email alerts
|

Bem-estar psicológico, enfrentamento e lipodistrofia em pessoas vivendo com HIV/AIDS

Abstract: RESUMO.Os objetivos do estudo foram investigar os efeitos da lipodistrofia sobre o bem-estar psicológico e a adesão ao tratamento anti-retroviral, e identificar as estratégias de enfrentamento utilizadas por pessoas soropositivas afetadas pela síndrome. Participaram 21 pessoas, com idades entre 29 e 52 anos, das quais quatorze eram homens. As entrevistas foram analisadas com base na análise de conteúdo categorial. Os resultados apontaram que a descoberta e a vivência da lipodistrofia podem afetar o bem-estar p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 7 publications
(8 reference statements)
0
5
0
9
Order By: Relevance
“…Upon finding out about possible adverse effects of medications, either from reading the medication insert or obtaining information from professionals or friends, some patients will experience more severe symptoms 1 . The anxiety symptoms seen in HIV carriers are related to uncertainties regarding the evolution of the disease and clinical progress, as well as fear of pain, suffering and physical deterioration, treatment and death 2 . These symptoms can also be characterized as a response to stressful situations, which vary according to the interpretation of each person.…”
Section: Introductionmentioning
confidence: 99%
“…Upon finding out about possible adverse effects of medications, either from reading the medication insert or obtaining information from professionals or friends, some patients will experience more severe symptoms 1 . The anxiety symptoms seen in HIV carriers are related to uncertainties regarding the evolution of the disease and clinical progress, as well as fear of pain, suffering and physical deterioration, treatment and death 2 . These symptoms can also be characterized as a response to stressful situations, which vary according to the interpretation of each person.…”
Section: Introductionmentioning
confidence: 99%
“…Considerando que el SS es un factor relevante en la evaluación de la CV y que las personas con la coinfección VIH / TB son más vulnerables debido a la doble infección, algunos autores traen como relevante la adhesión, el enfrentamiento y la CV en personas con VIH / aids (15) ; en el caso de TB, no se encontró ningún estudio específico, pero dada su magnitud en escenarios socioeconómicos desfavorables, el SS es citado como importante para la realización del tratamiento. La literatura nacional e internacional indica que el SS es un predictivo de mejora de las dimensiones de la CV (16,17) .…”
Section: Discussionunclassified
“…Los bajos escores encontrados en este ámbito acentúan el carácter de pauperización de ambas epidemias (25) . Las dificultades relativas a la condición socioeconómica sumadas a las dificultades de salud resultan en un número mayor de estresores, que repercuten negativamente en el bienestar psicológico y en la apreciación de la CV (15) .…”
Section: Discussionunclassified
“…Also noteworthy is that most relationships are negatively affected loving in general for those without a steady partner. 8 Regarding the identification of lipodystrophy, most respondents reported that the first signs of the disease were weight loss of face. Regarding lipohypertrophy 16 people are reported to fat gain in the abdominal region.…”
mentioning
confidence: 99%